Determinants and background of the educational and social pact in Spain - Esteban Frades, Santiago (Avances en Supervisión Educativa, 2010)
Nobody questions that signing a national educational contract is essential for our country and a long-time demand of Spanish society. The king of Spain himself, in his last years’ Christmas Speech was very explicit about it: "Its urgent, as I have emphasized for some time now, to sign a great contract on Education, and do it today better than tomorrow". It is very difficult, though. There are many vested interests at stake and teachers’ opinions are rather pessimistic about reaching an agreement that they regard as necessary but improbable. Besides, the older the interviewed ones are, the less chances they stand for the contract. After a revision of the education regulations that emerged out of agreements, this article describes some political and social contracts on Education.